New multiplicity results for critical p-Laplacian problems - Carlo Mercuri (Journal of Functional Analysis, 2022)
We prove new multiplicity results for the Brézis-Nirenberg problem for the p-Laplacian. Our proofs are based on a new abstract critical point theorem involving the Z2-cohomological index that requires less compactness than the (PS) condition.